Time to DTR: fan paratextualization about Game of Thrones last season - Moura, Bruno Melo; de Souza-Leão, André Luiz Maranhão (Revista de Administração da UFSM, 2022)
Purpose: Media products meaning lies on the interpretation of its content. As productive consumers, fans reframe them. In the process, they produce new texts on these products, known as paratexts. The research aims to understand how fan’s paratexts (re)produces discourses to re-signify media products’ (para)texts. For such, we look at fan paratextualization of Game of Thrones (GoT), an economic and cultural phenomenon with huge repercussions on social media. Design/methodology/approach: Through a Foucauldian Archeology, we collected and analyzed comments posted by GoT fans on promotional videos published on the TV series' official YouTube channel. Findings: The fans' paratextual production presents different positions on the consumed cultural product: a public tribute highlighting its cultural legacy that is based on feelings of nostalgia and frustration with the conclusion of its plot. We conclude that these paratexts worked as a reckoning for the TV series’ fans. Broadly, it is possible to interpret paratexts as marketing content that allow fans to act as prosumers of media products, the entertainment industry, and fans' culture. Originality/value: The study presents how the fans’ productive consumption is materialized through the paratext (re)production that both establish the resonance of media objects in the culture of fans and lead them to assume the role of co-authors of the texts they consume. This role reinforces how fans should be understood as consumers who can act freely in relation to marketing actions. Moreover, it implies that paratexts can be produced to stimulate the discursive production that works as prosumer performance of fans.